On the OCC Announcement Allowing US Banks to Use Stablecoins and the Immediate Impact on Cryptocurrency Valuations - Schaub, Mark (The Economics and Finance Letters, 2021)
On January 4, 2021 the Office of the Comptroller of the Currency (OCC), a major regulator of financial institutions in the United States, announced that federally chartered banks and thrifts were now allowed to utilize stablecoins as payment instruments. Much research and many discussions have revolved around policies of governments worldwide in how to handle the new cryptocurrency phenomenon. The purpose of this short study was to observe the valuation impact of that announcement on the three largest cryptocurrencies and two others. Research findings show the altcoins with valuations not tied to the dollar had substantial increases in value while the stablecoins, which the announcement specified are now allowed to be used by banks, changed very little. Specifically, Bitcoin and Etherium increased over 20% in value within 5 days of the announcement while the stablecoins Tether and USDCoin changed in value by no more than 0.10% for the same event window. This shows that stablecoins lived up to their name even though they were promoted as an acceptable payment system in the US.